The Evolving Landscape of Collaborative Writing in Literacy Education: A Systematic Bibliometric Review (2016-2025) - Syakur, Abdan; Sulfasyah, Sulfasyah; Bahri, Aliem (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study aims to explore the global landscape of research on Collaborative Writing in Literacy Education through a systematic bibliometric analysis. Using 364 Scopus-indexed publications from 2016 to 2025, the study maps trends in publication growth, influential authors, productive countries, and thematic evolution. Data were collected through a TITLE-ABS-KEY search with the keywords “collaborative writing” and “literacy” and analyzed using Microsoft Excel, VOSviewer, and Biblioshiny. The results indicate a steady increase in scholarly output, with the United States, United Kingdom, and Canada as dominant contributors, and emerging research from China, Indonesia, and Australia. The most active authors, including Ann Hill Duin and Isabel Pedersen, advanced studies on digital and academic literacy integration. Thematic mapping identified digital literacy, academic writing, and teacher education as core areas, while AI-assisted writing and critical literacy represent emerging trends. The study’s novelty lies in providing a comprehensive bibliometric synthesis that integrates thematic, co-authorship, and keyword analyses to reveal intellectual linkages and future directions. Practically, it guides educators and policymakers in adopting collaborative and technology-enhanced pedagogies that foster critical, digital, and reflective literacy. This study contributes to a deeper understanding of how collaboration transforms literacy learning in a digitally connected world.